Analytical study of ablution platforms and spaces in selected mosques of Selangor and Kuala Lumpur - Abdul Rahman, Julaila; Kamaruddin, Zumahiran; Jasmani, Ismail; Khairi, Mohammad Azim (2016)
This research aims to explore the various ablution platform found in Malaysian mosques focusing on those located in Kuala Lumpur and Selangor areas as case studies. Therefore, the objectives of this research are to determine the existing types of ablution platforms and spaces, and to analyze the design features and criteria of ablution platform and areas. Observation on physical studies of the collected samples from case studies has been done regarding its physical elements found at the mosques. Data collection has been analyzed by photo elicitation and line-up studies on the physical elements including design forms, dimensions, materials and safety. The results showed that there are two types of ablution platform; with seats and without seat. Both types of ablution platform are not user-friendly to the users especially PwDs. These includes inappropriate position of the seats and materials used at the ablution platform. In addition, the ablution platforms are lack of safety, cleanliness and hygiene.The study found that the ablution areas are not ergonomic and not well accessible for users particularly for elderly. This study recommends to improve the ablution platform to be more user-friendly facilities including the designs and arrangements of seats to ensure the smoothness of ablution activity.